RELATIONSHIP OF COMPENSATION, AND AUTHORITARY LEADERSHIP STYLES AND EMPLOYEE PERFORMANCE - Ely Rohmawati; Ani Wulandari (NAROTAMA UNIVERSITY, Indonesia, 2019)
This study aims to determine the relationship between compensation and authoritarian leadership style with employee performance at PT. Circle K Indonesia Utama Surabaya. The number of respondents in this study was 68 employees. The research method used is descriptive, validity test, reliability test, and spearman rank correlation calculation. The results showed that the compensation variables and authoritarian leadership style had a strong and significant relationship with employee performance. Strategies that can be applied by PT. Circle K Indonesia Utama Surabaya to improve employee performance, namely paying more attention to activities and providing employee compensation appropriately and accordingly. Also, improve the leadership style used by leaders.